MITIGATING CREDIT RISK IN BANKING: DETERMINING LIMIT VALUES FOR AUCTIONING MORTGAGE RIGHTS COLLATERAL IN ACCORDANCE WITH AUCTION REGULATIONS - Lastuti Abubakar; Tri Handayani (Universitas Syiah Kuala, 2025)
The Auction Implementation of Guidelines Regulation confirmed that the execution auction of collateral objects related to Mortgage Rights is a method designed to protect the rights of all parties involved. One of the key principles is the requirement to establish a limit value for mandatory auctions, including those related to Mortgage Rights. However, the current practices of execution auctions do not align with regulatory expectations that seek to ensure optimal pricing and a fair and legally certain process. Debtor objections to the determination of Limit Value and low selling prices have led to legal disputes against creditors. Therefore, an examination is essential to understand how risk mitigation can be achieved through the establishment of limit value. This study adopts a normative juridical approach with a descriptive-analytical research specification. The findings reveal that Articles 55-60 of Auction Implementation Guidelines Regulation outline the obligation to establish a limit value and provide criteria for determining that value. The establishment of limit value can function as a risk mitigation tool for Bank creditors, allowing them to adhere to prudential principles while providing legal certainty and protection for debtors, ultimately facilitating the attainment of the best possible price for their collateral objects.